Otherwise Worlds : Against Settler Colonialism and Anti-Blackness - Smith, Andrea, 1966-; Navarro, Jenell, 1978-; King, Tiffany Lethabo, 1976- (Book collections on Project MUSE., 2020)
"OTHERWISE WORLDS is an anthology motivated by the possibilities of other ways of being, feeling, thinking, and relating that exist outside of a settler-colonial, anti-Black ontology. In exploring the practices needed to access these possibilities, the editors and contributors call for new modes of understanding the intersections and tensions that hold Black and Indigenous communities in relation. Pushing past previous articulations of equivalence or incommensurability, solidarity or antagonism, the essays, interviews, and works of art that comprise the volume cohere around a singular, but multivocal, method: engaging with relation as a process, rather than a predetermined reality, in order to draw out the moments and spaces in which the "otherwise" might be reached. Navigating not only the formative debates that have brought Black studies and Indigenous studies scholars to the current impasse, but also the promises of otherwise futures, the editors and contributors read across difference and resist disciplining and disciplinary norms. The collection is divided into four interrelated thematic parts, each a series of provocations and engagements that highlight imaginative strategies and new forms of praxis. The first section considers otherwise potentialities through the corporeal form and the concerns of violence and pain that are themselves intrinsically bound to the body. Essays by Ashon Crawley and Denise Ferreira da Silva draw upon Hortense Spillers's invocation of flesh in order to confront understandings of corporeality focused on the sovereign body. The second section turns to Native studies scholars' use of land and conquest as analytics that productively unsettle the terrain of Black studies' inquiry (and draws a distinction between settler colonial studies and Native studies), with essays by Tiffany King and Chad Infante connecting the afterlives of slavery and conquest. The third section considers the possibilities of Black and Indigenous being-together as a site of both surveillance and resistance; essays by Maile Arvin and Cedric Sunray consider the erasure of Black and Indigenous socialities in the context of anti-Black racism among Native communities. The fourth and final section centers the crucial role of kinship in building future imaginaries through community and a more capacious understanding of relation. This section in particular draws upon artwork, notably that of Kimberly Robertson and Se'mana Thompson. This book will be of interest to readers in Black studies, Indigenous studies, and critical ethnic studies, as well as in feminist studies, queer studies, anthropology, sociology, and critical university studies"--